2008
DOI: 10.1136/bjsm.2008.050872
|View full text |Cite
|
Sign up to set email alerts
|

The reliability measurements of lateral scapular slide test at three different degrees of shoulder joint abduction

Abstract: SST did not show a consistent high reliability. The diagnostic accuracy of the LSST was low, which questions the clinical importance of the tests outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 17 publications
2
34
0
5
Order By: Relevance
“…To locate the trigger point, the point was marked with indelible ink, and the distance between this mark and the medial border of the scapula was measured with a caliper. 30 This mark established the site for all testing. Because of the criteria proposed by Simons, 7 the location for the follow-up measures was stable.…”
Section: Pressure-pain Thresholdmentioning
confidence: 99%
“…To locate the trigger point, the point was marked with indelible ink, and the distance between this mark and the medial border of the scapula was measured with a caliper. 30 This mark established the site for all testing. Because of the criteria proposed by Simons, 7 the location for the follow-up measures was stable.…”
Section: Pressure-pain Thresholdmentioning
confidence: 99%
“…It is used to determine scapular position with the upper extremity abducted to 0°, 45°, and 90° in the coronal plane. Some authors 2,3 suggested that measurements of scapular positioning based on the difference in side-to-side scapular distance measurements are not reliable and that the LSST should not be used to screen for shoulder dysfunction. Assessment of scapular position is based on the difference between bilateral scapular distances.…”
Section: Kiblermentioning
confidence: 99%
“…da [12] üç ayrı omuz eklem açısında LSST'nin güvenilirliğini araştırdıkları çalışmaların-da LSST 3 pozisyonunda spesivitenin düşük olduğunu belirtmektedir. Sonuçlar çalışmamızla uyumluluk göstermektedir.…”
Section: Tablo 4 Skapular Retraksiyon Testi Ve Skapular Yardım Testiunclassified
“…[2] Kronik kas-iskelet sistemi problemlerinin günlük yaşam aktivite fonksiyonlarında zorlanmalara neden olarak yaşam kalitesini azalttığı bilinmektedir. [8][9][10][11][12][13][14] Çalışmamızın amacı boyun, omuz ve boyun-omuz ağrılı olgularda, skapular diskinezi, ağrı ve esneklik arasındaki ilişkilerin araştırılmasıdır. Bireylerin boyun ve omuz ağrılarının değerlendi-rilmesi amacıyla Görsel Analog Skalası (GAS) kullanıldı.…”
Section: Introductionunclassified